Pelatihan Guru Dalam Peningkatan Literasi Siswa Melalui Pemanfaatan E-Modul Berbasis Ekopedagogi Berbantuan Kecerdasan Buatan - Alwi, Zahra; Ernalida; Nuzula, Khalidatun; Gunaika, Raka; Salsabila, Najla; Aulia, Putri Permata (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This Community Service Program (PkM) focuses on improving 21st-century student Literacy through the Utilization of Ecopedagogy-Based E-Modules Assisted by Artificial Intelligence (AI) at SMP Negeri 16 Palembang. The main problems identified were the low level of student literacy, as well as teachers' limitations in designing contextual and technology-adaptive learning, with most still relying on conventional methods (lectures). Initial observations indicated a gap in teacher knowledge, with 6 teachers stating they did not have adequate knowledge about the use of AI in education, and most required training in e-module development. In contrast, students showed high enthusiasm for the use of digital technology and environmental issues, although many found it difficult to find correct information on the internet. The solution offered was the implementation of Ecopedagogy and AI-based Interactive E-Modules to facilitate personalized learning, provide automatic feedback, and instill environmental values ​​and intentions from an early age. The implementation method used a Community-Based Participatory Education approach that actively involved teachers and students in a series of stages: Socialization, Training, Technology Application, Mentoring, and Evaluation. The training activities successfully improved teachers' understanding of 21st-century literacy concepts and their ability to create lesson plans that integrate ecopedagogy and AI applications as tools in content and assessment. This activity resulted in a concrete product in the form of ecopedagogy-based e-modules, with one example titled “Writing Environmentally Intelligent Poetry.” Overall, this activity received a positive response, improving teacher and student competency in utilizing AI-assisted technology, fostering ecological awareness, and laying the foundation for program sustainability through the establishment of a digital learning community and a scientific publication plan.